2003
DOI: 10.1210/jc.2003-030742
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Mannan-Binding Lectin in Patients with Type 1 Diabetes

Abstract: The hepatic protein mannan-binding lectin (MBL) activates the complement system on binding to carbohydrate patterns and is involved in first-line defense against invading microorganisms. Emerging evidence indicates that in some situations MBL may cause inexpedient complement activation and tissue injury through binding to endothelial glycosylations. MBL levels are suppressed by insulin treatment in critically ill patients, and, hypothetically, hepatic portal hypoinsulinemia could lead to increased levels of MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
107
6
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 32 publications
10
107
6
1
Order By: Relevance
“…These observations seem to contradict recent articles describing increased MBL concentrations in patients with type 1 diabetes with microvascular complications [29][30][31][32][33]. However, MBL plays a dual role in modifying inflammatory responses to injury [34].…”
Section: Discussionmentioning
confidence: 69%
“…These observations seem to contradict recent articles describing increased MBL concentrations in patients with type 1 diabetes with microvascular complications [29][30][31][32][33]. However, MBL plays a dual role in modifying inflammatory responses to injury [34].…”
Section: Discussionmentioning
confidence: 69%
“…In clinical trials, normoalbuminuric patients with type 1 diabetes have higher serum MBL levels than non-diabetic controls [4,5]. The groups had the same distribution of MBL genotypes [5].…”
Section: Discussionmentioning
confidence: 96%
“…Under normal conditions MBL does not bind to the body's own structures, but it does possess potential self-reactive properties. A significant association between serum MBL levels and renal function has been reported in normoalbuminuric, microalbuminuric and macroalbuminuric type 1 diabetic patients [4][5][6]. Furthermore, in a cohort study of type 1 diabetic patients followed for 18 years from diagnosis, serum MBL was a significant predictor of later renal impairment.…”
mentioning
confidence: 90%
“…Patients with type 1 diabetes and normal AER show increased levels of MBL when compared with healthy subjects; further, the MBL concentration was associated with AER even within the normoalbuminuric range while no correlation between MBL and C-reactive protein (CRP) was observed [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, low-grade inflammation and endothelial dysfunction may be a common denominator of microvascular and macrovascular complications [1][2][3], and it has been suggested that the activation of the complement system contributes to this cascade of inflammation [4].…”
Section: Introductionmentioning
confidence: 99%